The Existence of General Principles of Good Governance Regarding Discretion in the Implementation of Regional Government - Anggreni Atmei Lubis (Faculty of Law, Universitas Pekalongan, 2025)
The problem in this study focuses on AUPB based on Law No. 30 of 2014 concerning Government Administration and how the Existence of AUPB is related to Discretion in the Implementation of Regional Government. This study aims to determine the existence of AUPB, discretion in the implementation of regional government. The research method used is qualitative research with a normative legal research type. The research approach uses a descriptive analysis approach. The results of the study indicate that AUPB in Indonesia has been concretely regulated in Law No. 30 of 2014, where AUPB has a significant and urgent relationship with the authority of government officials in the use of discretion and the implementation of regional government. AUPB as a basis for reference in filing a lawsuit at the State Administrative Court. Discretion that is contrary to AUPB has an impact on the decision of the state administrative agency or official to become detournement de pouvoir or abuse of authority.